THE BIOLOGY OF SPINELESS CUTTLEFISH Sepiella inermis d’Orbigny IN THE NORT COASTAL WATER OF JAVA - Abdul Ghofar (JOURNAL OF COASTAL DEVELOPMENT, 1998)
A study was carried out to investigate the length-weight relationship, reproductive aspect, growth, and the relationship between beaks and body size of the spineless cuttlefish, Sepiella inermis d’Orbigny in the north coastal water of Java. The length-weight relationship varies relation to sexes; the slopes (b) are 2.147 for male and 2.436 for female, implying that the female attains a larger size at the same length. The fecundity of the species ranges from 145 to 225 eggs (taken by means of direct egg counting from individual having mantle length of 73-92 mm). The length at first maturity was estimate to be smaller in the male (73.24 mm) than in the female (91.63 mm). A growth model of the species is derived, based upon the data cuttlebone striations and mantle length. The life span of the species is estimated to be around 1 year, with a maximum mantle length of about 140 mm. The species grows rapidly, with curvature parameter of 2.413 yr1, and a hypothetical age t0 of -0.01 yr1. Lower hood length of the beaks show a strong, positive linear and exponential relationships respectively with mantle length and total body weight. Their potential use for biomass estimation, and for tropho-dynamic studies in the coastal water are indicated.